The Influence of Religion, Education and Socio-Cultural Values on Economic Development in Nigeria - Akinwumi Olatunji Samuel; Ajayi Oyedokun Samuel (Britain International for Academic Research (BIAR-Publisher), 2023)
Socio-cultural values refer to a set of values, beliefs, traditions and habits of a particular society that shape how people within that society approach risk and view careers. The values also influence their perceptions of money and ideas of an ideal lifestyle. Socio-cultural norms do not only affect how people relate and interact with their environment, they also influence how individuals within the society interact with the world and this in turn influence how they approach the process of economic developments. The thrust of this article is therefore to examine how religion, education and socio-cultural values influence economic development in Nigeria. Being an historical research, the paper employs historical method in its analysis. The findings of this paper reveal that religion and socio-cultural values such as materialism or post-materialism, collectivism or individualism, innovations, obedience, thrift and risk propensity, influence how individuals approach everyday activities, personal decisions on work, business venture, industrialization and by extension, economic development in Nigeria. The paper however concludes that the variable experiences of individuals during their development which include environmental factors, quality of education and relationship with others are dependent upon their socio-cultural backgrounds.